STANDARDS COMMITTEE Journey to Guidelines: Part One “Who ‘OR’ we?” - ORNAC, ORNAC (Operating Room Nurses Association of Canada Journal, 2016)
This is the first in a series of three articles outlining the process undertaken by the 2015-2017 ORNAC Standards Committee to transition from ‘Standards of Practice’ to ‘Guidelines for Practice’.